Respuesta :
First four terms of this sequence are:
[tex] f_0=f(0)=108,\\f_1=f(1)=\dfrac{2}{3}f(0)= \dfrac{2}{3}\cdot 108=72,\\f_2=f(2)=\dfrac{2}{3}f(1)= \dfrac{2}{3}\cdot 72=48,\\ f_3=f(3)=\dfrac{2}{3}f(2)= \dfrac{2}{3}\cdot 48=32 [/tex].
This sequence is decreasing and seems to be exponential. See whether you can determine such a and b, that [tex] f(x)=a\cdot b^x [/tex]:
1.
[tex] f(0)=a\cdot b^0=a,\\ f(0)=108 [/tex], then a=108,
2.
[tex] f(1)=108\cdot b^1=108 b,\\ f(1)=72 [/tex], then [tex] b=\dfrac{72}{108} =\dfrac{2}{3} [/tex].
3. Check for x=2 and x=3:
a) x=2:
[tex] f(2)=108\cdot \left(\dfrac{2}{3}\right)^2=108\cdot \dfrac{4}{9} =48 [/tex] (true),
b) x=3:
[tex] f(3)=108\cdot \left(\dfrac{2}{3}\right)^3=108\cdot \dfrac{8}{27} =32 [/tex] (true).
4. Check for all x:
[tex] f(x+1)=108\cdot \left(\dfrac{2}{3}\right)^{x+1},\\ f(x)=108\cdot \left(\dfrac{2}{3}\right)^x [/tex].
Equate f(x+1) and 2/3f(x):
[tex] 108\cdot \left(\dfrac{2}{3}\right)^{x+1}=\dfrac{2}{3}\cdot 108\cdot \left(\dfrac{2}{3}\right)^x ,\\\left(\dfrac{2}{3}\right)^{x+1}=\left(\dfrac{2}{3}\right)^{x+1} [/tex] is true equality for all x.
Answer: the graph is the graph of the function [tex]f(x)=108\cdot \left(\dfrac{2}{3}\right)^x [/tex].
Answer:
See picture attached.
Step-by-step explanation:
For x = 1, f(x) = 108. For the next x-value which is 2, that is, x+1, f(x+1) = (2/3)*f(x) = (2/3)*108 = 72. For the next x-value, which is 3, f(x+1) = (2/3)*f(x) = (2/3)*72 = 48 . For the next x-value, which is 4, f(x+1) = (2/3)*f(x) = (2/3)*48 = 32 . And so on.
x f(x)
1 108
2 72
3 48
4 32
